The Role of Endothelin-1 and Oxidative Stress In Pregnancy Induced Hypertension (Tikrit Journal of Pharmaceutical Sciences, 2023)
Pregnancy Induced HypertensionPIH is one of the most frequent complications of pregnancy , however little is known about its etiology. Endothelial dysfunction serves as a causative factor in the initiation of the maternal pathophysiological changes of PIH & is not just a result of this disorder. Endothelin-1 may play an important role in the pathophysiology of PIH, either by acting on vascular smooth muscle directly to induce contraction or by increasing the formation of angiotensin II. Pregnancy induced hypertension is associated with endothelial dysfunction & could be caused by oxidative stress. Recent evidence suggest the role of oxidative stress in PIH. The high level of malondiahyde MDA may reflect the excessive oxidative damage in PIH. The study sample consist of 50 normal non pregnant women, 50 normotensive pregnant women, and 50 preeclamptic pregnant women in their third trimester in Mosul city. The aim of this study was designed to evaluate the role of endothelial dysfunction and oxidative stress in pathogenesis of PIH. The results of this study showed that there was a highly significant elevation (P0.000) in the serum level of endothelin-1 in the preeclamptic pregnant women in comparison with normotensive pregnant & the control group. Also there was a highly significant elevation (P0.000) in the level of serum MDA in the preeclamptic pregnant women in comparison with normotensive pregnancy & the control group. The serum endothelin-1 has a significant negative correlation with both maternal age & gestational age, while endothelin-1 has a significant positive correlation with diastolic blood pressure. The MDA showed a significant negative correlation with maternal age, while there was a significant positive correlation between MDA & diastolic blood pressure.